Resection of gallbladder remnants after subtotal cholecystectomy: presentation and management. Issue 11 (November 2018) - Concors, Seth J.; Kirkland, Matthew L.; Schuricht, Alan L.; Dempsey, Daniel T.; Morris, Jon B.; Vollmer, Charles M.; Drebin, Jeffery A.; Lee, Major K.
Abstract: Background: Subtotal cholecystectomy (SC) involves removal of a portion of the gallbladder typically due to hazardous inflammation. While this technique reliably prevents common bile duct (CBD) injury, future procedures can be required if the gallbladder remnant becomes symptomatic. The morbidity associated with resection of gallbladder remnants in patients that previously underwent SC is reviewed. Methods: Records for patients having undergone redo cholecystectomy for symptomatic gallbladder remnants in a tertiary care system from 2013 to 2017 were retrospectively reviewed. Results: Fourteen patients underwent repeat cholecystectomy. Five surgeons dictated the initial procedure as a subtotal cholecystectomy. All patients returned with symptomatic cholelithiasis between zero months and seven years after the index cholecystectomy. Redo cholecystectomy was attempted laparoscopically in two patients but ultimately required an open approach in all. One patient had a recognized CBD injury requiring a hepaticojejunostomy, and a second patient had a minor wound infection. Symptoms resolved in 13/14 patients. Conclusions: Redocholecystectomy (RC) for gallbladder remnants has been detailed in case reports, but no sizable North American series have been presented. These results illustrate a drawback to the reconstituting technique of SC. RC effectively resolves symptoms but requires adherence to safe principles of cholecystectomy and is one indication for an open approach.